Allergic Rhinitis in Childhood - Review - Arzu Babayiğit; Özkan Karaman (Güncel Pediatri)
Allergic rhinitis, an immunoglobulin E mediated disease, is the most common chronic allergic childhood disease. The disease is characterized by nasal sneezing, rhinorrhea, palate and eye itchiness, and congestion and it can significantly impact children’s health. It causes uncomfortable symptoms, impairs quality of life and can predispose to the development of comorbidities such as asthma. Etiological diagnosis is based on cutaneous prick tests, which have a high sensitivity and specificity rate and which can be easily applied to young children. Treatment initially involves avoidance measures and, when necessary, pharmacotherapy or immunotherapy. Pharmacotherapy generally involves antihistamines and/or nasal corticosteroids, but leukotriene antagonists have also demonstrated effectiveness in treating allergic rhinitis symptoms. In this article, the symptoms, diagnosis and treatment of allergic rhinitis in childhood are discussed. (Journal of Current Pediatrics 2010; 8: 105-12)